Centralize retail application and customization (CRAC) in Malaysian perspective / Azuree Hydani Misri - Misri, Azuree Hydani (2002)
Transforming from traditional retail business to electronic retail business is important for retailers who want to grow their business and gain competitive advantage. Many retailers take a shortcut transforming to online business without analyzing the potential risk and problems. Consequently many of them fail and fall back to traditional methods. Retailers do not realize the importance of business model for e-tailing to support the business growth as well as organizing changes. It seems like retailers and consumers need a new platform or business model to encourage their involvement in electronic retailing. Thus, the introduction of new CRAC (Centralize Retail Application & Customization) business model perhaps will brings the alternative solution for electronic retailing to success. This research paper will discuss about the CRAC business model as a new platform for electronic retailing in Malaysia. The research includes the study of retail business, retail information system, electronic marketplace, technology infrastructure and online consumer behavior in Malaysia.